Effects of radiation and surgery on healing of femoral fractures in a rat model1. Issue 8 (19th April 2013) - Nicholls, Fred; Janic, Katarina; Filomeno, Paola; Willett, Thomas; Grynpas, Marc; Ferguson, Peter
Abstract Management of soft tissue sarcoma involves multimodality treatment, including surgery and radiotherapy. Pathologic fracture of the femur after such treatment in the thigh is one serious, late complication and nonunion rates of 80–90% are reported. We hypothesize that the combination of radiotherapy and periosteal stripping (during tumor resection) leads to greater impairment of the fracture repair process than either intervention alone. Female Wistar retired breeder rats were randomized into four treatment groups (control, radiotherapy, surgery, and combination of radiotherapy and surgery) and three end‐points (21, 28, and 35 days post‐fracture). Designated animals first underwent radiotherapy, followed by surgical stripping of the periosteum 3 weeks later and femoral fracture with fixation after another 3 weeks. Animals were sacrificed and fractures examined using microCT and histomorphometry. Simple transverse or short oblique femoral fractures were produced. By 35 days, control animals formed unions, periosteum‐stripped animals formed hypertrophic non‐unions and irradiated animals formed atrophic non‐unions. Histomorphometry revealed an absence of chondroid and osteoid production in animals undergoing radiotherapy. The relative contribution of periosteal stripping to occurrence of non‐union was statistically insignificant. Radiation prior to fracture reliably resulted in atrophic non‐union in our model. The contribution of periosteal stripping was negligible. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1323–1331, 2013